2021
DOI: 10.3390/medicina57050429
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Patellofemoral Pain Syndrome with Dielectric Radiofrequency Diathermy: A Preliminary Single-Group Study with Six-Month Follow-Up

Abstract: Background and Objectives: Notwithstanding patellofemoral pain syndrome (PFPS) being one of the most common causes of pain in the front of the knee in outpatients, few studies have shown the effects of radiofrequency on knee pain and function in this population. The aim of the present study was to determine whether outpatients diagnosed with PFPS obtained improvement in pain and function after treatment by dynamic application of monopolar dielectric diathermy by emission of radiofrequency (MDR). Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Cabello et al described the efficacy of diathermy in managing pain and functional disability in patients with patellofemoral pain syndrome. Hence, this study has shown that diathermy by emission of radio-frequency is a good option that should be applied on large scale for treating other musculoskeletal issues as well 20 .…”
Section: Discussionmentioning
confidence: 87%
“…Cabello et al described the efficacy of diathermy in managing pain and functional disability in patients with patellofemoral pain syndrome. Hence, this study has shown that diathermy by emission of radio-frequency is a good option that should be applied on large scale for treating other musculoskeletal issues as well 20 .…”
Section: Discussionmentioning
confidence: 87%
“…Previous research has focused on actively strengthening the quadriceps vastus medialis oblique (VMO) coupled with manual treatment, tape patella realignment, stretching, and therapeutic exercise (Willy et al, 2019). However, despite the need for quadriceps exercises, numerous interventions focusing on single muscle strengthening have failed with their theoretical rationale (Albornoz-Cabello et al, 2021) because the patients need to understand their condition, and the importance of strengthening exercises is unknown. Therefore, it is a need for a patient's know the value of therapeutic strengthening in curing their conditions; if not, the strengthening could fail.…”
Section: Therapeutic Strengthening For Quadricepsmentioning
confidence: 99%
“…Kumaran and Watson defined the deep blood flow changes that appear with the application of RFD, which enhances blood support to soft tissues [ 1 ]. Other authors focused their research on the analgesic effects of RFD on musculoskeletal [ 8 , 9 , 10 ], neuropathic [ 11 ], myofascial [ 12 ] and post-surgery pain [ 13 ]. Nevertheless, Gold et al [ 14 ] reviewed its efficacy in feminine rejuvenation, suggesting improvements in mild to moderate conditions related with vaginal laxity and neocollagenesis proliferation [ 15 ], despite the lack of robustness in the quality of the studies found [ 14 ].…”
Section: Introductionmentioning
confidence: 99%